Kontaminasi Aflatoxin dalam Rantai Distribusi Kacang Tanah di Indonesia - A. A. Rahmianna; Joko Purnomo (Iptek Tanaman Pangan, 2015)
The substance is very toxic, which may cause health problem when consumed by human or by animal. of the twelve aflatoxin members, the B1-aflatoxin was reported as the most prevalence in Indonesia, and it was also the most toxic. Therefore, B1-aflatoxin was used as a criterion for the maximum tolerable limit of aflatoxin content in food and feed stuff. Aflatoxin B1 contamination was reported on groundnut grains sold in the retail traditional markets throughout Indonesia. The contaminated grains were noted derived from the nationally produced as well as from the imported ones. The aflatoxin contamination increased as the grain of groundnut reached the final retail markets destination. Contaminated grain processed into various food retained the aflatoxin in a toxic form. The negative effect on health from consuming food contaminated by aflatoxin must be minimized. The government of Indonesia had established food safety regulation regarding aflatoxin contamination, but prevention through the proper cultural practices and post harvest handling of groundnut, were equally important measure.